Dark lessons. Crime and detection on campus. - Muller, M., Pronzini, B. (New York MACMILLAN PUBLIISHING COMPANY, 1985)
The halls of academe from kindergarden the college-may seem an unlikely place for murder and may seem, but according to Marcia Muller and Bill Pronzini, in fiction they are often crowded with sinister characters bent on wicked undertalkings.
Keywords: Literature